Pendampingan Pemasaran Digital, Analisis Data dan Akuntansi pada Koperasi Produsen Berkah Sejahterah Bersama di Surabaya - Utomo, Sulistyo Budi; Dewi, Mega Arisia; Sidharta, R Yudi; Suprihhadi, Heru; Widiarma, In’am (Universitas Pahlawan Tuanku Tambusai, 2025)
The formation of a cooperative cannot be separated from the cooperative's articles of association itself, the cooperative's articles of association are guidelines or rules of the game for all activities and operations of the Cooperative. The agreement that has been stated in the articles of association and of course adjusted to the Cooperative's SOP. The Berkah Sejahterah Bersama producer cooperative is a forum for developing the businesses of MSMEs, most of whom are producers who have businesses that produce food and beverages. The implementation method is by holding a meeting held at the place of one of the Cooperative members with direction given by the STIESIA Academics such as digital marketing, data analysis and Accounting, then to follow up on the event, comprehensive assistance is provided for all MSME actors involved, providing supervision based on Cooperative law. The results of community service activities for MSME members in the city of Surabaya have gone well. This activity is quite important for cooperative members on how to run according to the rules agreed upon together and is useful for improving the welfare of Cooperative members